2019
DOI: 10.1016/j.yhbeh.2019.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Rewritable fidelity: How repeated pairings and age influence subsequent pair-bond formation in male prairie voles

Abstract: The prairie vole has proven a valuable animal model for the neurobiological study of social monogamy and pair bonding. Previous research has focused almost exclusively on virgin prairie voles forming pair-bonds for the first time -a paradigm with limited relevance to human social behavior. In the present study, we used stud males to assess the impact of repeated pair-bond formation and dissolution on the behaviors and neurobiology relevant to subsequent pair-bond formation. Stud males were tested for behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 28 publications
3
23
2
Order By: Relevance
“…It is worth noting that at a superficial level, our results and those of Kenkel et al (2019), which indicate that preference formation is common even following multiple pairings, may seem at odds with reports that only ~20% of male and female prairie voles re-pair in the wild (Carter and Figure 4. Effects of mating latency on partner preference.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…It is worth noting that at a superficial level, our results and those of Kenkel et al (2019), which indicate that preference formation is common even following multiple pairings, may seem at odds with reports that only ~20% of male and female prairie voles re-pair in the wild (Carter and Figure 4. Effects of mating latency on partner preference.…”
Section: Discussioncontrasting
confidence: 89%
“…Thus, these conditions were behaviorally equivalent with respect to the behaviors displayed towards their first partner. Similar to previous reports by Kenkel et al (2019), we found that voles in all conditions were capable of showing a preference for their second partner within 3 days of pairing (short-term; 48 Hour p = 0.022, 2 Week p = 0.003, 4 Week p = 0.075 (but see significant distance data), Fig. 3: A, D, G).…”
Section: Stability For Preference For Partner 2 Depends On Separation Timesupporting
confidence: 91%
See 2 more Smart Citations
“…The extended‐duration partner preference test has also been adapted to assess preference for individuals exhibiting different characteristics related to but beyond basic familiarity. For example, the test has been used to test preference for new versus former partners in prairie voles (Harbert, Pellegrini, Gordon, & Donaldson, 2020), preference for huddling with a group versus a single partner in same‐sex meadow voles (Ondrasek et al., 2015), preference for gonadally intact versus gonadectomized subjects, preference for same‐ versus opposite‐sex individuals (DeVries et al., 1997), and changes with age and repeated pairing (Kenkel et al., 2019).…”
Section: Commentarymentioning
confidence: 99%